Older women in the criminal justice system: a brief report from a nominal group - Robinson, Louise (The journal of forensic psychiatry & psychology, 2025)
There are increasing numbers of older women in prison in England and Wales. The needs of older women in prison have been under researched and are often unmet. This paper explores staff and expert perspectives on the needs of older women in prison through a nominal group attended by six participants, including a consultant at the UK Health Security Agency; a General Practitioner; a postgraduate student completing a project on older women in prison; an academic researcher with expertise on older women in prison; a National Women’s Health, Social Care, and Environment Review Group lead; and a HMMPS Diversity and Inclusion Lead. Six key themes were identified: 1) health screening; 2) health services and unmet health needs; 3) emotional wellbeing; 4) social and family connections; 5) the need for a professional’s forum; and 6) limited data and research. Participants agreed that this population’s needs are not adequately met. Moving forward, structures must be put in place to ensure that older women’s needs are understood and met, and their voices heard.